Self-Concept as Mediator between Social Supports and Health Character; a Path Analysis - Firdaus, Syamsul; Suhariadi, Fendy; Soedirham, Oedojo; Setyowati, Anggi (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
Adolescents with drug abuse are common, especially among students. Health character is needed to prevent this behavior.  Health character relates to family support, peer support, teacher support (social supports) and self-concept as the mediator between these supports and health character. This study was observational study and used cross sectional design to analyze self-concept as the mediator between social supports (family support, peer support, and teacher support) and health character. Data was collected from senior high school students in Banjarbaru, South Kalimantan for two months. We used cluster random sampling also self-report questionnaires to collect the data. AMOS was used to calculate coefficient path and model fit. Sobel test was used to calculate the strength of self-concept as the mediator between social supports and health character. The results showed that the final model of social supports, self-concept and health character with GFI, AGFI, CFI, and RMSEA were 0.994, 0.996, 0.992, and 0.103. Our findings showed that self-concept was full mediator between teacher support and health character (p < 0.05). Self-concept was partial mediator between family support and health character (p < 0.05). Further research is needed to develop intervention and prevent drug abuse based on health character model. Keywords: Drug abusers, Social supports, Self-concept